Principal's Strategy in Developing Islamic Education Work Plan (Rks/M) - Maszeri; Mokhlis; Ali Nurhadi; Faridatul Jannah (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2025)
In education to make schools more advanced and developed every year, a school work plan (RKS) is needed. The RKS is prepared to determine school actions within a period of 4 years by taking into account the availability of the school, both from documents, descriptions, visions and missions of the school to achieve the goals and objectives that have been set. Strategies that can be applied by the principal in preparing the RKS are: effective communication with TPS, becoming a resource person or facilitator, conducting monitoring and evaluation, implementing alternative methods such as FGD, Workshop, Delphi and so on. The results of this paper are: the development of a school work plan or RKS through the role of the principal can be done by continuously compiling, directing, guiding teachers and staff so that the quality of education in schools can advance and develop in the next 4 years. and is in a national standard position. The steps taken are preparation, preparation, ratification or approval of the RKS.